2022
DOI: 10.1097/sap.0000000000003157
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Affirming Surgeries

Abstract: Background Gender affirmation surgery is an exponentially growing field within plastic surgery. The aim of our study is to analyze demographics, procedure type, trends, and outcomes in the surgical management of gender identity disorder in the past few years. Methods The American College of Surgeons NSQIP database was queried for the years 2015 to 2019. International Classification of Diseases codes were used to identify all gender-affirming cases. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…These findings are consistent with 2 previous population-based studies which report significant growth in GAS over the last 20 years, though those studies lack granularity to report on incidence of specific procedures. 2,3 The marked rise seen in our study may reflect a build-up of demand prior to Medicaid expansion in NYS. Nationwide, one study querying GAS from 2000 to 2014 found that the number of patients covered by Medicaid or Medicare increased threefold from 2012-2013 to 2014.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…These findings are consistent with 2 previous population-based studies which report significant growth in GAS over the last 20 years, though those studies lack granularity to report on incidence of specific procedures. 2,3 The marked rise seen in our study may reflect a build-up of demand prior to Medicaid expansion in NYS. Nationwide, one study querying GAS from 2000 to 2014 found that the number of patients covered by Medicaid or Medicare increased threefold from 2012-2013 to 2014.…”
Section: Discussionmentioning
confidence: 73%
“…Using the NYS HCUP (Healthcare Cost and Utilization Project) State Inpatient Database from 2008 to 2017, we identified all adult patients ≥18 years old with an ICD-9/10 diagnosis of gender dysphoria using a previously described method for identifying transgender individuals in claims data (Supplementary Appendix, https://www.urologypracticejournal.com). 2,3,7,8 Of those, we identified patients who underwent genital GAS—phalloplasty or vaginoplasty—using ICD-9/10 procedure codes (Supplementary Appendix, https://www.urologypracticejournal.com).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be due to prolonged recovery time and higher complication rates in genital surgeries. 3,13,[20][21][22] Studies have shown that level of independence was significantly worse after GAS, which might lead to worse satisfaction scores for patients who underwent genital surgeries. 23 Our study showed that non-White patients had higher VMP-G scores before and after GAS, compared with White patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients who underwent chest surgeries reported higher scores in satisfaction domain (20.4 vs 18.4, P = 0.02). This might be due to prolonged recovery time and higher complication rates in genital surgeries 3,13,20–22 . Studies have shown that level of independence was significantly worse after GAS, which might lead to worse satisfaction scores for patients who underwent genital surgeries 23 .…”
Section: Discussionmentioning
confidence: 99%